2010
DOI: 10.1007/s00412-010-0276-7
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar targeting of coilin is regulated by its hypomethylation state

Abstract: Coilin, a molecular marker for Cajal bodies (CBs), is a phosphoprotein that contains a cryptic nucleolar localization signal and multiple interacting domains, such as the RG-box. Post-translational symmetrical dimethylation of arginines on the coilin RG-box is required for the recruitment of the survival motor neuron (SMN) protein and splicing small ribonucleoproteins (snRNPs) to CBs. Here, we analyze the role of the methylation state of coilin in the regulation of its localization to the nucleolus. We use the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…The efficiency of the siRNA was confirmed by immunoblotting ( (Lemm et al, 2006). This coilin reorganization is consistent with previous studies showing nucleolar accumulations of coilin upon the experimental disruption of CBs (Tapia et al, 2010;Gilder and Hebert, 2011) and with our recent observation that SMN depletion in human motor neurons from SMA patients causes CB loss and nucleolar relocalization of coilin (Tapia et al, 2012).…”
Section: Smn Is a Novel Sumo1 Substratesupporting
confidence: 88%
“…The efficiency of the siRNA was confirmed by immunoblotting ( (Lemm et al, 2006). This coilin reorganization is consistent with previous studies showing nucleolar accumulations of coilin upon the experimental disruption of CBs (Tapia et al, 2010;Gilder and Hebert, 2011) and with our recent observation that SMN depletion in human motor neurons from SMA patients causes CB loss and nucleolar relocalization of coilin (Tapia et al, 2012).…”
Section: Smn Is a Novel Sumo1 Substratesupporting
confidence: 88%
“…However, the cap-like Cajal bodies observed upon Fam118B overexpression were not formed around the nucleolus, suggesting that this morphological change in Cajal bodies might reflect an unknown status of these structures. Nevertheless, previous studies have revealed a close crosstalk between nucleoli and Cajal bodies, because many components shuttle between these two structures, including coilin, fibrillarin and Nopp140 (Isaac et al, 1998;Tapia et al, 2010). In line with these observations, we showed that although residues 190-232 of Fam118B are required for the targeting of Fam118B to Cajal bodies, Fam118B mutants (M2, M4 and M6) without this motif translocate to nucleoli.…”
Section: Discussionsupporting
confidence: 88%
“…3b). Some immunogold particles appeared scattered over nucleoplasm, presumably corresponding to the nucleoplasmic pool of coilin (Nizami et al 2010;Tapia et al 2010). In motor neurons of the SMA patient, the immunolabeling was detected in typical CBs (Fig.…”
Section: Resultsmentioning
confidence: 97%